1996
DOI: 10.1021/ma951769c
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Kinetics of Vinyl Polyperoxides

Abstract: This is the first report on studies carried out in detail on high-pressure oxygen copolymerization (>50 psi) of the vinyl monomers styrene and R-methylstyrene (AMS). The saturation pressure of oxygen for AMS oxidation, hitherto obscure, is found to be 300 psi. Whereas the ease of oxidation is more favorable for styrene, the rate and yield of polyperoxide formation are higher for AMS. This is explained on the basis of the reactivity of the corresponding alkyl and peroxy radicals. Below 50 °C, degradation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 17 publications
3
56
0
Order By: Relevance
“…The saturation pressure of oxygen for styrene (STY) and α ‐methylstyrene (AMS) was found to be 2 and 300 psi, respectively 11. During the oxidative polymerization, STY shows auto‐deceleration with a break point, whereas AMS12 exhibits auto‐acceleration with the formation of a knee point 11.…”
Section: Introductionmentioning
confidence: 99%
“…The saturation pressure of oxygen for styrene (STY) and α ‐methylstyrene (AMS) was found to be 2 and 300 psi, respectively 11. During the oxidative polymerization, STY shows auto‐deceleration with a break point, whereas AMS12 exhibits auto‐acceleration with the formation of a knee point 11.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a peroxide polymer is formed in a high yield during the oxidative polymerization of styrene, but the simultaneous formation of benzaldehyde and formaldehyde is unavoidable and influences the polymerization kinetics and the reaction mechanism including a radical chain transfer. 8,12,27,28 The accurate evaluation of the thermal properties of peroxide polymers is often hin- dered by contamination with decomposition products despite a large number of studies on the synthesis and characterization of peroxide polymers.…”
mentioning
confidence: 99%
“…A detailed examination of the mechanism of oxidative polymerization revealed that the polyperoxides formed during oxygen copolymerization undergo facile degradation above 50°C [32]. To avoid side reactions, we have studied kinetics of oxidative polymerization at 40-50°C.…”
Section: Kinetics Of Oxidative Polymerizationmentioning
confidence: 99%
“…The [M] and [I] are monomer and initiator concentration, and k a is the overall rate constant for the oxidative copolymerization. [32] of the electrondonating methyl group. In addition to the reactivity of ÀMO 2 toward the monomer, we have to also consider the electron richness of the vinyl p bond in the monomer.…”
Section: Kinetics Of Oxidative Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation